Linking pregnancy- and birth-related risk factors to a multivariate fusion of child cortical structure - Linn R. S. Lindseth; Dani Beck; Lars T. Westlye; Christian K. Tamnes; Linn B. Norbom (Proceedings of the National Academy of Sciences, 2025)
Pregnancy- and birth-related factors affect offspring brain development, emphasizing the importance of early life exposures. While most previous studies have focused on a few variables in isolation, here we investigated associations between a broad range of pregnancy- and birth-related variables and multivariate cortical brain MRI features. Our sample consisted of 8,396 children aged 8.9 to 11.1 y from the Adolescent Brain Cognitive Development Study. Through multiple correspondence analysis and factor analysis of mixed data, we distilled numerous pregnancy and birth variables into four overarching dimensions; maternal pregnancy complications, maternal substance use, low birth weight and prematurity, and newborn birth complications. Vertex-wise measures of cortical thickness (CT), surface area (SA), and curvature were fused using linked independent component analysis. Linear mixed-effects models showed that maternal pregnancy complications and low birth weight and prematurity were associated with smaller global SA. Additionally, low birth weight and prematurity was associated with complex regional cortical patterns reflecting bidirectional variations in both SA and CT. Newborn birth complications showed multivariate patterns reflecting smaller occipital- and larger temporal area, bidirectional frontal area variations, and reduced CT across the cortex. Maternal substance use showed no associations with child cortical structure. By employing a multifactorial and multivariate morphometric fusion approach, we connected complications during pregnancy and fetal size and prematurity to global SA and specific regional signatures across child cortical MRI features.